The Role of Profitability in Mediating Financial Efficiency on Indonesian Firm Value - Ragis Arginta Resian; Nor Norisanti; Kokom Komariah (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
The Consumer Non-Cyclicals sector occupies a strategically vital role in Indonesia ‘s economy by supplying essential goods and services that sustain societal consumption stability across various economic conditions. Despite these defensive characteristics, average stock prices in the sector declined persistently from IDR 1,441 in 2023 to IDR 1,389 in 2025, signalling mounting pressure on firm value. This study examines the mediating role of profitability in the relationship between managerial administrative decisions, specifically Cash Conversion Cycle (CCC) management and operating costs efficiency (BOPO) and firm value (PER) among Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the 2023-2025 period. Employing a quantitative causal-associative design, 108 companies were selected through purposive sampling from a population of 132, generating 324 firm-year observations. Data were analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) via SmartPLS v3.2.9. Results indicate that CCC and operating costs do not directly affect firm value. However, both negatively and significantly influence profitability (ROA), which in turn positively and significantly affects firm value. Profitability mediates both relationships, confirming its role as the critical transmission mechanism through which operational and administrative efficiency translates into market valuation. These findings carry significant practical implications for managers, business practitioners, and economic policymakers in designing strategies that link operational discipline to sustained business value creation.